The magnetization reversal and high temperature dielectric response in Y1−xHoxFe0.5Cr0.5O3. Issue 9 (July 2016) - Shi, L.R.; Xia, Z.C.; Huang, S.; Xiao, G.L.; Jin, Z.; Wei, M.; Chen, B.R.; Shang, C.; Cheng, H.; Ouyang, Z.W.
Abstract: The structural, magnetic, and dielectric properties of the Y1− x Ho x Fe0.5 Cr0.5 O3 ( x =0, 0.05, 0.1, 0.3, and 0.5) compounds have been investigated. Rietveld refinement of the XRD patterns shows that the compounds possess orthorhombic perovskite structure. The dual magnetization reversal is observed in the samples with x =0.05 and 0.1, and it vanishes when x ≥0.3. Ferromagnetic-like behavior with large coercive fields is observed in all Ho 3+ doped YFe0.5 Cr0.5 O3 samples, indicating a doping induced metamagnetic behavior. This abnormal magnetization behavior can be explained by the antiparallel magnetic coupling between the Ho 3+ and the canted Cr 3+ /Fe 3+ moments, as well as the Ho–O–Ho magnetic interaction. The dielectric behavior in the frequency range from 100 Hz to 10 MHz is investigated. The low doped samples ( x =0, 0.05, and 0.1) exhibit relaxation-like dielectric behavior and colossal dielectric constant in a wide temperature and frequency range. The dual magnetization reversal under low magnetic field makes these materials attractive candidates for the magnetic dual sensor devices.